Consumer Protection in Digital Transactions: An Evaluation of Regulation and the Effectiveness of Law Enforcement - Anwar Anwar; Samsudin Arifin Dabamona; Harry A Tuhumury (PT. Anagata Sembagi Education, 2025)
This study examines the protection of consumers in digital transactions in Indonesia by evaluating existing regulations and the effectiveness of law enforcement. With the rapid expansion of Indonesia’s digital economy, consumer rights face increasing challenges due to gaps in legal frameworks and enforcement mechanisms. Key laws analysed include the Consumer Protection Law, the Electronic Information and Transactions Law, and the Personal Data Protection Law. While these regulations lay foundational protections, they often lack specificity and adaptability to the dynamic digital marketplace. The enforcement landscape is constrained by limited resources, fragmented institutional coordination, and insufficient judicial expertise, which hamper effective resolution of consumer disputes. A comparative analysis with jurisdictions such as the European Union and Singapore reveals best practices in regulatory clarity, empowered supervisory bodies, and consumer education that Indonesia could adopt. Empirical data highlights the urgency of reform as digital transactions and related consumer complaints grow rapidly. The study recommends legislative updates tailored to digital commerce, enhanced enforcement capacity through specialised authorities, and strengthened consumer awareness initiatives. These measures aim to establish a more robust and responsive consumer protection system, fostering trust and fairness in Indonesia’s digital economy. The findings contribute to ongoing discourse on balancing innovation and consumer rights in the digital age.